Air-processed organic tandem solar cells on glass: Toward competitive operating lifetimes - Adams, Jens; Spyropoulos, Georgios; Salvador, Michael Filipe; Li, Ning; Strohm, Sebastian; Lucera, Luca; Langner, Stefan; Machui, Florian; Zhang, Hong; Ameri, Tayebeh; Voigt, Monika M.; Krebs, Frederik C.; et al. (Energy and Environmental Science, 2015)
Photovoltaic devices based on organic semiconductors (OPVs) hold great promise as a cost-effective renewable energy platform because they can be processed from solution and deposited on flexible plastics using roll-to-roll processing. Despite important progress and reported power conversion efficiencies of more than 10% the rather limited stability of this type of devices raises concerns towards future commercialization. The tandem concept allows for both absorbing a broader range of the solar spectrum and reducing thermalization losses. We designed an organic tandem solar cell with an inverted device geometry comprising environmentally stable active and charge-selecting layers. Under continuous white light irradiation, we demonstrate an extrapolated, operating lifetime in excess of one decade. We elucidate that for the current generation of organic tandem cells one critical requirement for long operating lifetimes consists of periodic UV light treatment. These results suggest that new material approaches towards UV-resilient active and interfacial layers may enable efficient organic tandem solar cells with lifetimes competitive with traditional inorganic photovoltaics.

A solution-processable star-shaped molecule for high-performance organic solar cells via alkyl chain engineering and solvent additive - Min, Jie; Luponosov, Yuriy N.; Ameri, Tayebeh; Elschner, Andreas; Peregudova, Svetlana M.; Baran, Derya; Heumüller, Thomas; Li, Ning; Machui, Florian; Ponomarenko, Sergei; Brabec, Christoph (Organic Electronics, 2013)
A new star-shaped D-π-A molecule, tris4-[5′′-(1,1- dicyanobut-1-en-2-yl)-2,2′-bithiophen-5-yl]phenylamine N(Ph-2T-DCN-Et), with high efficiency potential for photovoltaic applications was synthesized. As compared to its analogue S(TPA-bT-DCN), it showed stronger absorption in the region of 350-450 nm and a lower lying highest occupied molecular energy level (HOMO). Solution-processed organic solar cells (OSCs) based on a blend of N(Ph-2T-DCN-Et) and PCBM resulted in a high PCE of 3.1% without any post-treatment. The PCE of N(Ph-2T-DCN-Et) based solar cells was further improved to 3.6% under simulated AM 1.5 by addition of a new additive 4-bromoanisole (BrAni). © 2012 Elsevier B.V. All rights reserved.
Keywords: 4-Bromoanisole (BrAni); D-π-A molecule; Highest occupied molecular energy level; Organic solar cells (OSCs)

A universal method to form the equivalent ohmic contact for efficient solution-processed organic tandem solar cells - Li, Ning; Stubhan, Tobias; Krantz, Johannes; Machui, Florian; Turbiez, Mathieu; Ameri, Tayebeh; Brabec, Christoph (Journal of Materials Chemistry A, 2014)
The highly transparent, conductive and robust intermediate layer (IML) is the primary challenge for constructing efficient organic tandem solar cells. In this work, we demonstrate an easy but generic approach to realize the fully functional, solution-processed IMLs. In detail, solution-processed silver-nanowires are packed at low concentration between hole- and electron-transporting layers to convert an otherwise rectifying interface into an ohmic interface. The IMLs are proven to be of ohmic nature under applied bias, despite the unipolar charge selectivity of the single layers. Ohmic recombination within IMLs is further proven in organic tandem solar cells fabricated by doctor-blading under ambient conditions. The tandem solar cells based on PCDTBT:[70]PCBM as the bottom cell and pDPP5T-2:[60]PCBM as the top cell give a power conversion efficiency of 7.25%, which is among the highest values for solution-processed organic tandem solar cells fabricated by using a roll-to-roll compatible deposition method in air. © the Partner Organisations 2014.
Keywords: Engineering controlled terms: Hole concentration; Nanowires; Ohmic contacts Ambient conditions; Deposition methods; Electron-transporting layers; Intermediate layers; Low concentrations; Power conversion efficiencies; Solution-processed; Tandem solar cells Engineering main heading: Solar cells

Cost analysis of roll-to-roll fabricated ITO free single and tandem organic solar modules based on data from manufacture - Machui, Florian; Hosel, Markus; Li, Ning; Spyropoulos, Georgios; Ameri, Tayebeh; Sondergaard, Roar R.; Jorgensen, Mikkel; Scheel, Arnulf; Gaiser, Detlef; Kreul, Kilian; Lenssen, Daniel; Legros, Mathilde; et al. (Energy and Environmental Science, 2014)
We present a cost analysis based on state of the art printing and coating processes to fully encapsulated, flexible ITO- and vacuum-free polymer solar cell modules. Manufacturing data for both single junctions and tandem junctions are presented and analyzed. Within this calculation the most expensive layers and processing steps are identified. Based on large roll-to-roll coating experiments the exact material consumptions were determined. In addition to the data for the pilot scale experiment presented here, projections to medium and large scale scenarios serve as a guide to achieve cost targets of 5 €ct per W in a detailed material and cost analysis. These scenarios include the replacement of cost intensive layers, as well as process optimization steps. Furthermore, the cost structures for single and tandem devices are listed in detail and discussed. In an optimized model the material costs drop below 10 € per m which proves that OPV is a competitive alternative to established power generation technologies. This journal is © the Partner Organisations 2014.
Keywords: Engineering controlled terms: Coatings; Costs; Experiments; Manufacture; Optimization; Rolls (machine components); Solar cells Coating process; Optimized models; Pilot-scale experiments; Polymer Solar Cells; Power generation technology; Processing steps; Single junction; Tandem junction Engineering main heading: Cost accounting GEOBASE Subject Index: coating; cost-benefit analysis; numerical model; photovoltaic system; solar power

Determination of phase diagrams of binary and ternary organic semiconductor blends for organic photovoltaic devices - Li, Ning; Machui, Florian; Waller, David; Koppe, Markus; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2011)
Ternary blends were recently suggested as a sound approach to increase the short circuit current density of organic solar cells by sensitizing the bulk heterojunction (BHJ) with a further absorber, i.e., a low band gap polymer. Poly[2,6-(4,4-bis-(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b́]dithiophene) -alt-4,7(2,1,3-benzothiadiazole)] (PCPDTBT) is a suitable candidate as low band gap polymer for ternary blends with poly(3-hexylthiophene) (P3HT) and [6,6]-pheny-C-butyric acid methyl ester ([60]PCBM) due to its ideal energy level and charge carrier properties. Phase diagrams are common in polymer science to visualize the mixing behavior of multicomponent systems as a function of temperature. In this study, we have used differential scanning calorimetry (DSC) to extract phase diagrams for binary and ternary organic semiconductor blends, and built the corresponding solar cells to analyze correlations between the thermal and the electrical properties of such semiconductor blends. © 2011 Elsevier B.V. All rights reserved.
Keywords: Differential scanning calorimetry (DSC); Organic photovoltaic devices; P3HT/PCBM/PCPDTBT; Phase diagram; Ternary blends

Determination of solubility parameters for organic semiconductor formulations - Machui, Florian; Abbott, Steven; Waller, David; Koppe, Markus; Brabec, Christoph (Macromolecular Chemistry and Physics, 2011)
The concept of Hansen solubility parameters (HSP) is applied to organic semiconductors in order to determine and predict their solubility behavior, which is essential for the design of functional and environmentally friendly ink formulations for organic photovoltaics. Two different conjugated polymers, one semicrystalline and one dominantly amorphous, and one fullerene derivative are selected as prototype candidates to evaluate the applicability of the HSP concept for organic semiconductors. The method for determining the solubility parameters is described and the quality of the HSP fits as well as their suitability for designing of organic electronic inks are discussed in detail. The applicability of Hansen solubility parameters in designing organic semiconductor ink formulations is analyzed by determining and predicting the solubility behavior of three different organic semiconductors. A large number of solvents are studied and temperature-dependent solubility is examined to enhance the practical relevance of this work. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: conjugated polymers; fullerenes; Hansen solubility parameters (HSP); ink formulations; organic photovoltaics

Determination of the P3HT:PCBM solubility parameters via a binary solvent gradient method: Impact of solubility on the photovoltaic performance - Machui, Florian; Langner, Stefan; Zhu, Xiangdong; Abbott, Steven; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2012)
We discuss an alternative route to determine the solubility parameters of two prototype organic semiconductors, namely the semi-crystalline polymer poly-(3-hexylthiophene-2,5-diyl) (P3HT) and the methano-fullerene derivative [6,6]-phenyl-C -butyric acid methyl ester (PCBM). The HSP (Hansen solubility Parameters) derived by this novel method are compared to the findings derived from the classical multi-solvent method to determine the HSP, and significantly higher accuracy is found. For this novel approach we designed two component solvent blend systems, being composed by mixing a solvent with a non-solvent. Varying the composition of the solvent non-solvent blends from 0% to 100% gradually converts a solvent into a non-solvent. This very accurate control of the dispersive, polar and hydrogen contributions to the overall solubility now allows determining the Hansen sphere for P3HT and PCBM with much higher accuracy. The transition from a solvent into a non-solvent was further followed by solar cell investigations. Comparing the solubility studies with device investigations allows identifying the processing limits of solvent systems. © 2012 Elsevier B.V. All rights reserved.
Keywords: Conjugated polymers; Fullerenes; Hansen solubility parameters; Ink formulations; Organic photovoltaics; Solvent blends

Determining the coating speed limitations for organic photovoltaic inks - Jakubka, Florian; Heyder, Madeleine; Kaschta, Joachim; Machui, Florian; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2013)
To determine the output capability of present organic photovoltaic (OPV) materials, it is important to know the theoretical maximum coating speeds of the used semiconductor formulations. Here, we present a comprehensive investigation of the coating stability window of several prototype organic semiconductor inks relevant for organic solar cells. The coating stability window was first determined experimentally by a sheet to sheet coater at velocities of up to 10 m/min. A numerical simulation model based on the "Coating Window Suite 2010" software was established to give insight into the coating stability limitations at higher coating velocities. An analysis of PEDOT:PSS [poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate)] in a water/isopropyl alcohol mixture as well as P3HT:PCBM [poly(3-hexylthiophene-2,5-diyl):Phenyl-C61-butyric acid methyl ester] in chlorobenzene, o-xylene and tetrahydronaphthalene showed the possibility of coating speeds up to 60 m/min. The simulation further revealed the maximum coating head distances for a given wet film thickness. Finally, we show a solar-cell with slot-die coated PEDOT:PSS and P3HT:PCBM-layer based on the parameters obtained by the simulated data, which exhibits reasonable performance. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: OPV solar cell; Slot-die coating; Coating speed

Flexible organic tandem solar modules: A story of up-scaling - Spyropoulos, Georgios; Kubis, Peter; Li, Ning; Lucera, Luca; Salvador, Michael Filipe; Baran, Derya; Machui, Florian; Ameri, Tayebeh; Voigt, Monika; Brabec, Christoph (Organic Photovoltaics XV, 2014)
The competition in the field of solar energy between Organic Photovoltaics (OPVs) and several Inorganic Photovoltaic technologies is continuously increasing to reach the ultimate purpose of energy supply from inexpensive and easily manufactured solar cell units. Solution-processed printing techniques on flexible substrates attach a tremendous opportunity to the OPVs for the accomplishment of low-cost and large area applications. Furthermore, tandem architectures came to boost up even more OPVs by increasing the photon-harvesting properties of the device. In this work, we demonstrate the road of realizing flexible organic tandem solar modules constructed by a fully roll-to-roll compatible processing. The modules exhibit an efficiency of 5.4% with geometrical fill factors beyond 80% and minimized interconnection-resistance losses. The processing involves low temperature (<70 °C), coating methods compatible with slot die coating and high speed and precision laser patterning.
Keywords: Flexible solar cells; Laser patterning; Organic solar modules; Organic tandem solar cells; Solution-processing

High precision processing of flexible P3HT/PCBM modules with geometric fill factor over 95% - Kubis, Peter; Lucera, Luca; Machui, Florian; Spyropoulos, Georgios; Cordero, Johann; Frey, Alfred; Kaschta, Joachim; Voigt, Monika; Matt, Gebhard; Zeira, Eitan; Brabec, Christoph (Organic Electronics, 2014)
Flexible OPV modules, based on P3HT:PCBM as absorber layer, were manufactured with a power conversion efficiency over 3% and for a total area of 3500 mm(2) consisting of 14 in series interconnected cells. The modules utilize the excellent mechanical and the outstanding optical properties of sputtered transparent ITO-Metal-ITO (IMI) electrodes deposited on the PET foil on the one hand, and the combination of large area slot-die coating with high resolution ultrafast laser patterning on the other hand. The manufacturing of modules with outstanding performance was found to be reproducible. The right combination of innovative electrodes and smart roll-to-roll compatible processing technologies demonstrates a viable path towards high efficient industrial module technology. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Flexible transparent electrode; Flexible OPV module; Slot-die coating; Ultra-fast laser patterning; High geometric fill factor

High shunt resistance in polymer solar cells comprising a MoO3 hole extraction layer processed from nanoparticle suspension - Stubhan, Tobias; Ameri, Tayebeh; Salinas Batallas, Michael; Krantz, Johannes; Machui, Florian; Halik, Marcus; Brabec, Christoph (Applied Physics Letters, 2011)
In this report, we present solution processed molybdenum trioxide (MoO3) layers incorporated as hole extraction layer (HEL) in polymer solar cells (PSCs) and demonstrate the replacement of the commonly employed poly(3,4-ethylene dioxythiophene):(polystyrene sulfonic acid) (PEDOT:PSS). MoO3 is known to have excellent electronic properties and to yield more stable devices compared to PEDOT:PSS. We demonstrate fully functional solar cells with up to 65 nm thick MoO3 HEL deposited from a nanoparticle suspension at low temperatures. The PSCs with an active layer comprising a blend of poly(3-hexylthiophene) and [6,6]-phenyl-C61 butyric acid methyl ester and a MoO3 HEL show comparable performance to reference devices with a PEDOT:PSS HEL. The best cells with MoO3 reach a fill factor of 66.7% and power conversion efficiency of 2.92%. Moreover, MoO3 containing solar cells exhibit an excellent shunt behavior with a parallel resistance of above 100 kΩ cm2.

Influence of a ternary donor material on the morphology of a P3HT:PCBM blend for organic photovoltaic devices - Machui, Florian; Rathgeber, Silke; Li, Ning; Ameri, Tayebeh; Brabec, Christoph (Journal of Materials Chemistry, 2012)
A comparison of grazing incidence wide-angle X-ray scattering (GiWAXS) and differential scanning calorimetric measurements (DSC) was used to identify the influence of a dominantly amorphous small band gap polymer material poly[2,6-(4,4-bis-(2-ethylhexyl)-4H-cyclopenta[2,1-b;3,4-b′]dithiophene) -alt-4,7(2,1,3-benzothiadiazole)] (PCPDTBT) on the crystallinity of a semi-crystalline polymer/fullerene composite. In binary blends the low band gap polymer does not influence the crystalline part of P3HT, but does influence the crystallinity of the fullerene. In ternary blends, a significant drop of the PCBM crystallinity is observed with increasing PCPDTBT content. Adding more than 20 wt% PCPDTBT to a P3HT:PCBM blend leads to a dramatic reduction of device efficiency, mainly due to short circuit current density and fill factor losses. This deterioration is attributed to the fact that addition of more than 20 wt% PCPDTBT to the host system strongly reduces crystallinity of the fullerene phase and electron transport in the ternary system. © 2012 The Royal Society of Chemistry.
Keywords: 2; 1; 3-Benzothiadiazole; Binary blends; Crystallinities; Device efficiency; Differential scanning calorimetric measurements; Electron transport; Fill factor; Grazing incidence; Low bandgap polymers; Organic photovoltaic devices; Semi-crystalline polymer; Small band gap polymer; Ternary blends; Wide angle X-ray scattering Engineering controlled terms: Crystalline materials; Energy gap; Fullerenes; Polymer blends Engineering main heading: Polymers

Large area slot-die coated organic solar cells on flexible substrates with non-halogenated solution formulations - Machui, Florian; Lucera, Luca; Spyropoulos, Georgios; Cordero, Johann; Ali, Abid Shaukat; Kubis, Peter; Ameri, Tayebeh; Voigt, Monika; Brabec, Christoph (Solar Energy Materials and Solar Cells, 2014)
The transfer from lab scale to industrial application is one of the challenges for organic photovoltaics. For this, non halogenated formulations are a decisive need for the upscaling process, as are roll-to-toll (R2R) compatible methods. Devices processed with o-xylene using slot-die coating as a sheet-to-sheet technique show a reduced efficiency on a larger scale compared to lab scale solar cells. By using a mixture of high and low volatile solvents which selectively dissolve one component, the film homogeneity and the efficiency is dramatically improved. The slot-die coated active layers for solar cells processed from non-halogenated solvents show device efficiencies above 3% on flexible substrates.
Keywords: Film homogeneity; Flexible substrates; Ink formulation; Organic photovoltaics; Slot-die coating; Solvent

Low temperature, solution processed metal oxide buffer layers fulfilling large area production requirements - Stubhan, Tobias; Litzov, Ivan; Li, Ning; Wang, Hao; Krantz, Johannes; Machui, Florian; Steidl, M.; Oh, H.; Matt, Gebhard; Brabec, Christoph (Proceedings of SPIE, 2012)
This paper is a review of our previous work on the field of low temperature, solution processed metal oxide buffer layers published in various journals. Our work focuses on zinc oxide (ZnO) and aluminum-doped zinc oxide (AZO) as n-type and molybdenum oxide (MoO3) as p-type solution processed buffer layer. In addition to that, we investigate the surface modification of AZO using phosphonic acid-anchored aliphatic and fullerene self assembled monolayers (SAMs
Keywords: Aluminum-doped zinc oxide; Low temperatures; Metal oxides; P-type; Phosphonic; Production requirements; Solution-processed; Zinc oxide (ZnO) Engineering controlled terms: Aluminum; Metallic compounds; Molybdenum oxide; Optical waveguides; Organic acids; Self assembled monolayers; Temperature; Zinc oxide Engineering main heading: Buffer layers

Morphology analysis of near IR sensitized polymer/fullerene organic solar cells by implementing low bandgap heteroanalogue C-/Si-PCPDTBT - Ameri, Tayebeh; Khoram, Parisa; Heumüller, Thomas; Baran, Derya; Machui, Florian; Troeger, Anna; Sgobba, Vito; Guldi, Dirk Michael; Halik, Marcus; Rathgeber, Silke; Scherf, Ullrich; Brabec, Christoph (Journal of Materials Chemistry A, 2014)
In the current work, we have investigated the morphological aspects of the ternary solar cells based on host matrices of P3HT:PCBM and P3HT:ICBA, using the low bandgap polymer analogues of C- and Si-bridged PCPDTBT as near IR sensitizers, which show noticeably different performance. A direct comparison of these well-functional and poorly functional ternary blend systems provides insights into the bottlenecks of device performance and enables us to set up an initial set of design rules for ternary organic solar cells. Our study reveals the importance of surface energy as a driving force controlling sensitizer location and morphology formation of ternary blends. The interfacial surface energy results indicate that Si-PCPDTBT locates at amorphous interfaces and P3HT crystallites, while C-PCPDTBT tends to accumulate at amorphous interfaces and semi-crystalline (or agglomerated) domains of the fullerene derivatives. GIWAXS and SCLC results support this prediction where adding high content of C-PCPDTBT influences mainly the semi-crystallinity (aggregation) of the fullerene and reduces the electron mobility, but Si-PCPDTBT impacts mainly the P3HT ordering and, in turn, deteriorates the hole mobility. These findings show that the disruption of the fullerene semi-crystalline domains is more detrimental to the device performance than the disruption of the polymer domains.

Nano-morphology characterization of organic bulk heterojunctions based on mono and bis-adduct fullerenes - Azimi, Hamed; Fournier, Darcy; Wirix, Maarten; Dobrocka, Edmund; Ameri, Tayebeh; Machui, Florian; Rodman, Sheila; Dennler, Gilles; Scharber, Markus C.; Hingerl, Kurt; Loos, Joachim; Brabec, Christoph; et al. (Organic Electronics, 2012)
We have studied organic bulk heterojunction photovoltaic devices based on a bridged-bithiophene donor-acceptor type low-band gap polymer blended with PCBM and bis-PCBM. The impact of the molecular arrangement is discussed in terms of the correlation between the solar-cell performance and the degree of crystallization. Differential scanning calorimetry (DSC) and grazing-incidence X-ray diffraction (GIXRD) prove that films with bis-PCBM typically result in more amorphous blends than comparable films with PCBM. Electron tomography (ET) is used to visualize the three dimensional morphology of photoactive layers, confirming the presence of nanofibers, formed in different scales through the thickness in the blended films with mono and bis-fullerenes. © 2012 Elsevier B.V. All rights reserved.
Keywords: Bis-PCBM; Crystallinity; Morphology; Organic photovoltaic; PCBM

Near IR sensitization of polymer/fullerene solar cells - Ameri, Tayebeh; Min, Jie; Li, Ning; Machui, Florian; Brabec, Christoph; Forster, Michael; Schottler, Kristina; Dolfen, Daniel; Allard, Sybille; Scherf, Ullrich (Organic Photovoltaics XIII, 2012)
In this work we discuss an elegant, alternative strategy to extend the spectral sensitivity of wide bandgap polymers in the near IR region. We discuss the microstructure of different functional ternary systems and compare them from different perspectives. © 2012 SPIE.
Keywords: IR sensitization; Organic solar cells; Small bandgap polymers; Ternary blends

Patterning of organic photovoltaic modules by ultrafast laser - Kubis, Peter; Li, Ning; Stubhan, Tobias; Machui, Florian; Matt, Gebhard; Voigt, Monika; Brabec, Christoph (Progress in Photovoltaics: Research and Applications, 2015)
In this paper, we demonstrate that laser patterning of organic solar cells by ultrafast laser systems (pulse length <350 fs) is an attractive process to produce photovoltaic modules with outstanding high geometric fill factors. Moreover, in terms of precision, registration, and debris generation and in terms of keeping the damage to the underneath layers at a minimum, ultrafast laser patterning with a pulse length of few hundreds of femtoseconds turns out to yield superior results. Ablation of all three different solar cell layers (electrodes (P1 and P3) and interfaces and semiconductor (P2)) is achieved with a single wavelength simply by a precise adjustment of the laser fluence and the patterning overlap. Camera positioning allows a precise registration between the various processing steps and a reduction of the width of the overall interconnection regime to the hundreds of micrometers dimension, resulting in high geometrical fill factors of over 90% for monolithically interconnected organic solar cell modules.
Keywords: Femtosecond pulses; Laser patterning; Organic solar cells; PV module

Performance enhancement of the p3ht/pcbm solar cells through nir sensitization using a small-bandgap polymer - Ameri, Tayebeh; Min, Jie; Li, Ning; Machui, Florian; Baran, Derya; Forster, Michael; Schottler, Kristina J.; Dolfen, Daniel; Scherf, Ullrich; Brabec, Christoph (Advanced Energy Materials, 2012)

Printing high performance reflective electrodes for organic solar cells - Krantz, Johannes; Forberich, Karen; Kubis, Peter; Machui, Florian; Min, Jie; Stubhan, Tobias; Brabec, Christoph (Organic Electronics, 2015)
In this paper we solve a long term material problem of thin film organic electronics, namely the solution processing of an opaque electrode. Solution processing of opaque metallic top electrodes typically leads to severe shunting problems. We solve this issue by reversing the electrode sequence and print a highly conductive but opaque bottom electrode from metallic precursors. Devices based on these printed bottom electrodes are compared to reference stacks based on evaporated silver. The transparent top electrode is solution processed from silver nanowire inks, which results in highly transparent electrodes with excellent conductivity. The optical, mainly reflective properties of the opaque silver electrode are investigated in comparison to screen-printed silver pastes. The outstanding smoothness of the printed Ag electrode results in high reflectivity and poly(3-hexylthiophene-2,5-diyl):[6,6]-phenyl-C61-butyric acid methyl ester (P3HT:PCBM) based solar cells with η >. 2.5% and high fill factors performing on par with reference devices on evaporated silver electrode layers.
Keywords: Highly reflective electrode; Printed silver precursor ink; Solution processable electrode; Substrate architecture; Superstrate architecture

Round-Robin studies as a method for testing and validating high-effi ciency ito-free polymer solar cells based on roll-to-roll-coated highly conductive and transparent flexible substrates - Larsen-Olsen, Thue T.; Machui, Florian; Lechene, Balthazar; Berny, Stephane; Angmo, Dechan; Sondergaard, Roar; Blouin, Nicolas; Mitchell, William; Tierney, Steven; Cull, Tobias; Tiwana, Priti; Meyer, Frank; et al. (Advanced Energy Materials, 2012)
Photovoltaic cells based on organic and polymer materials (OPVs) are celebrated as being a possible solution to the energy needs of the future, [ 1b ] and, with record effi ciencies having breached the 10% milestone accompanied by emerging involvement from the materials industry, expectations are rapidly approaching reality. [ 1c ] However, in order to move OPVs beyond the individual laboratory and into a generally applied setting, scientists need to limit the gap between carefully prepared hero devices and the large-scale manufacture of thousands of devices. We propose that this is done by urgently attending to the challenges of scalability and reproducibility. In this communication, we demonstrate an approach using round-robin testing as a method to validate effi ciency measurements of OPVs based on semitransparent electrodes on fl exible substrates, with and without indium tin oxide (ITO). ITO-free substrates were rollto- roll coated under ambient conditions and were truly scalable. Our results demonstrate inherent uncertainties in the device-effi ciency data, with variations in the carefully measured effi ciency data for the same device between highly qualifi ed laboratories as high as 25%, depending on the substrate and its active area. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.

Scalable, ambient atmosphere roll-to-roll manufacture of encapsulated large area, flexible organic tandem solar cell modules - Andersen, Thomas R.; Dam, Henrik F.; Hosel, Markus; Helgesen, Martin; Carle, Jon E.; Larsen-Olsen, Thue T.; Gevorgyan, Suren A.; Andreasen, Jens W.; Adams, Jens; Li, Ning; Machui, Florian; Spyropoulos, Georgios; et al. (Energy and Environmental Science, 2014)
Inline printing and coating methods have been demonstrated to enable a high technical yield of fully roll-to-roll processed polymer tandem solar cell modules. We demonstrate generality by employing different material sets and also describe how the ink systems must be carefully co-developed in order to reach the ambitious objective of a fully printed and coated 14-layer flexible tandem solar cell stack. The roll-to-roll methodologies involved are flexographic printing, rotary screen printing, slot-die coating, X-ray scattering, electrical testing and UV-lamination. Their combination enables the manufacture of completely functional devices in exceptionally high yields. Critical to the ink and process development is a carefully chosen technology transfer to industry method where first a roll coater is employed enabling contactless stack build up, followed by a small roll-to-roll coater fitted to an X-ray machine enabling in situ studies of wet ink deposition and drying mechanisms, ultimately elucidating how a robust inline processed recombination layer is key to a high technical yield. Finally, the transfer to full roll-to-roll processing is demonstrated. This journal is © the Partner Organisations 2014.
Keywords: Engineering controlled terms: Coatings; Manufacture; Technology transfer; Testing Ambient atmosphere; Flexographic printing; Functional devices; Polymer tandem solar cells; Process development; Recombination layers; Roll-to-roll processing; Rotary screen printing Engineering main heading: Solar cells GEOBASE Subject Index: coating; photovoltaic system; polymer; solar power; technological development

Solubility Based Identification of Green Solvents for Small Molecule Organic Solar Cells - Burgues-Ceballos, Ignasi; Machui, Florian; Min, Jie; Ameri, Tayebeh; Voigt, Monika M.; Luponosov, Yuriy N.; Ponomarenko, Sergei A.; Lacharmoise, Paul D.; Campoy-Quiles, Mariano; Brabec, Christoph (Advanced Functional Materials, 2014)
Replacing halogenated solvents in the processing of organic solar cells by green solvents is a required step before the commercialization of this technology. With this purpose, some attempts have been made, although a general method is yet to be developed. Here, the potential of the Hansen solubility parameters (HSP) analysis for the design of green ink formulations for solution-processed active layer in bulk heterojunction photovoltaic devices based on small molecules is demonstrated. The motivation of moving towards organic small molecules stems from their lower molecular weight and more definite structure which makes them more likely to be dissolved in a wider variety of organic solvents. In the first step, the HSP of selected active materials are determined, namely, the star-shaped D-π-A tris[4-[5′′-(1,1-dicyanobut-1-en-2-yl)-2,2′-bithiophen-5-yl]pheny]amine N(Ph-2T-DCN-Et)3 small molecule and fullerene derivative [6,6]-phenyl-C71-butyric acid methyl ester (PC70BM). Secondly, computer simulations based on HSP allow the prediction of suitable green solvents for this specific material system. The most promising green solvents, according to the simulations, are then used to fabricate solar cell devices using pristine solvents and two solvents mixtures. These devices show power conversion efficiencies around 3.6%, which are comparable to those obtained with halogenated solvents. This good performance is a result of the sufficient solubility achieved after a successful prediction of good (green) solvents.
Keywords: Hansen solubility parameters; ink formulations; non-halogenated solvents; organic photovoltaics; small molecule

Solubility, Miscibility, and the Impact on Solid-State Morphology - Brabec, Christoph; Machui, Florian (Wiley-VCH, 2013)
Keywords: Glass transition temperature; Miscibility; Organic semiconductors; Phase diagram; Solar cells; Solubility

Tailoring green formulation: Printing and upscaling of inverted organic solar cells - Voigt, Monika; Machui, Florian; Lucera, Luca; Spyropoulos, Georgios; Cordero, Johann; Kubis, Peter; Ali, Abid Shaukat; Shalan, Ahmed E.; Brabec, Christoph (39th IEEE Photovoltaic Specialists Conference, PVSC 2013, 2013)
By tailoring the solvents of active organic solar cell layers regarding their solubility (Hansen parameters), non-halogenated solvents and solvent mixtures can be used to print the active layers of organic solar cells. Similar efficiencies to other typical laboratory methods as spin-coating can be reached. Furthermore, using sheet-to-sheet printing or coating techniques compatible to mass-manufacturing and structuring by laser ablation, we can upscale to 10×20 cm and manufacture modules on plastic substrates. This is a breakthrough for organic solar cells and the next important step on the way to utilize organic solar cells for industrial manufacturing. © 2013 IEEE.
Keywords: Green solvents; P3HT:PCBM; Photovoltaic cells; Printing; Simulation; Solubility

Towards 15% energy conversion efficiency: A systematic study of the solution-processed organic tandem solar cells based on commercially available materials - Li, Ning; Baran, Derya; Forberich, Karen; Machui, Florian; Ameri, Tayebeh; Turbiez, Mathieu; Carrasco-Orozco, Miguel; Drees, Martin; Facchetti, Antonio; Krebs, Frederik C.; Brabec, Christoph (Energy and Environmental Science, 2013)
Owing to the lack of scalable high performance donor materials, studies on mass-produced organic photovoltaic (OPV) devices lag far behind that on lab-scale devices. In this work, we choose 6 already commercially available conjugated polymers and systematically investigate their potential in organic tandem solar cells. All the devices are processed under environmental conditions using doctor-blading, which is highly compatible with mass-production coating technologies. Power conversion efficiencies (PCE) of 6-7% are obtained for OPV devices based on different active layers. Optical simulations based on experimental data are performed for all realized tandem solar cells. An efficiency potential of ∼10% is estimated for these compounds in combination with phenyl-C-butyric acid methyl ester (PCBM) as an acceptor. In addition, we assume a hypothetical, optimized acceptor to understand the limitation of donors. It is suggested that a PCE of >14% is realistic for tandem solar cells based on these commercially available donor materials. Along with the demonstration of novel intermediate layers we believe that this systematic study provides valuable insight for those attempting to realize the high efficiency potential of tandem architectures. © 2013 The Royal Society of Chemistry.
Keywords: Coating technologies; Environmental conditions; Novel intermediates; Optical simulation; Organic photovoltaic devices; Power conversion efficiencies; Solution-processed; Tandem solar cells Engineering controlled terms: Conversion efficiency Engineering main heading: Solar cells GEOBASE Subject Index: coating; energy efficiency; numerical model; optimization; photovoltaic system